Chlamydia trachomatisinfection prevalence and serovar distribution in a high‐density urban area in the north of Italy. Issue 6 (June 2016) - Foschi, Claudio; Nardini, Paola; Banzola, Nicoletta; D'Antuono, Antonietta; Compri, Monica; Cevenini, Roberto; Marangoni, Antonella
Abstract : N/A: The aim of this study was to assess Chlamydia trachomatis (CT) infection prevalence and serovar distribution in a high‐density urban area in the north of Italy, by comparing different groups of subjects divided on the basis of the type of care provider they referred to (STI Clinic, gynaecologists or general practitioners). From January 2011 to May 2014, all the specimens submitted to the Microbiology Laboratory of St Orsola Hospital in Bologna for CT detection were tested by PCR assay. For positive specimens, molecular genotyping based on RFLP analysis was performed. Total prevalence of CT infection was 8.1 %, with significant differences between subgroups ( P <0.01) but stable during the study period. The STI Clinic was mainly responsible for CT diagnosis, whereas the lowest infection prevalence was detected in gynaecological clinics, despite the high number of tests performed. Extra‐genital samples were almost exclusively collected from males at the STI Clinic. Interestingly, 13.3 % of patients providing extra‐genital specimens were positive for CT on rectal and/or pharyngeal swabs, and 4.4 % of cases would have been missed if extra‐genital sites had not been tested. The most common serovar was E, and serovar distribution was influenced by gender ( P <0.01), age ( P <0.01), care provider ( P =0.01) and anatomical site ( P <0.01). The L2 serovar was detected only in extra‐genital samples from males at the STI Clinic. Knowledge about care providers' contributions in CT testing and diagnosis is essential for infection control. CT typing is crucial for appropriate management of specific infections, such as lymphogranuloma venereum in extra‐genital samples of high‐risk populations.